Pax3 synergizes with Gli2 and Zic1 in transactivating the Myf5 epaxial somite enhancer - Himeda, Charis L. (2013)
Both Glis, the downstream effectors of hedgehog signaling, and Zic transcription factors are required for Myf5 expression in the epaxial somite. Here we demonstrate a novel synergistic interaction between members of both families and Pax3, a paired-domain transcription factor that is essential for both myogenesis and neural crest development. We show that Pax3 synergizes with both Gli2 and Zic1 in transactivating the Myf5 epaxial somite (ES) enhancer in concert with the Myf5 promoter. This synergy is dependent on conserved functional domains of the proteins, as well as on a novel homeodomain motif in the Myf5 promoter and the essential Gli motif in the ES enhancer. Importantly, overexpression of Zic1 and Pax3 in the 10T1/2 mesodermal cell model results in enrichment of these factors at the endogenous Myf5 locus and induction of Myf5 expression. In our previous work, we showed that by enhancing nuclear translocation of Gli factors, Zics provide spatiotemporal patterning for Gli family members in the epaxial induction of Myf5 expression. Our current study indicates a complementary mechanism in which association with DNA-bound Pax3 strengthens the ability of both Zic1 and Gli2 to transactivate Myf5 in the epaxial somite.